The design and implementation of accelerated authentication system for mobile platform - LiPing Du; Ying Li; GuiFen Zhao (2010 International Conference on Information, Networking and Automation (ICINA), 2010)
This paper designs and implements an accelerated authentication system for mobile platform. This system is based on CSK (combined symmetric key) algorithm and cipher chip technology. It can generate the authentication code which is one-time-one-variant for the mobile terminal and reach to the goal of accelerated authentication. Compared to the popular WPKI certificate for mobile platform, this system can improve the authentication speed and cuts the costs of maintenance, deployment and training.